Risk Factors for Tailor Workers with the Incident of Flak Pain at PT X - Dewi Zuniawati (IKIP Mataram, 2023)
Flank pain is a type of problem in the musculoskeletal system. This condition causes pain that appears both on the right and on the left, behind the waist, precisely in the area below the ribs and above the pelvis. Back pain is still a problem from the decline in work productivity in various parts of the world. The purpose of this study is to analyze job risk factors, namely length of sitting, sitting position, and length of work and to find the most influential occupational risk factors among the 3 variables. Research method Quantitative research design through a